MAJOR DEPRESSIVE DISORDERS AND PERSISTENT DEPRESSIVE DISORDERS AMONGPHARM.D STUDENTS: A CROSS SECTIONAL STUDY - Sheikh Abdul Khaliq; Sheikh Abdul Khaliq; Soﬁa Aslam; Sher Ali; Wasim Anwar Lone; Muhammad Din; Sajjad Ahmed (Journal of University Medical & Dental College, 2019)
BACKGROUND: Depression among students of Pharmacy and Health Sciences is common. Pharmacy students and professionals deal with patients, making it imperative for them to have normal mental health. Pharmacists play key role in the management of mental illnesses by counseling drug related issues. The main aim of study is to evaluate the magnitude of depression among Pharm.D students in diﬀerent universities. SUBJECTS AND METHODS: Cross sectional study was conducted during July 2017 to December 2017. Data has been collected from 456 Pharm.D students of four major universities of Karachi. Sample size was determined by precision analysis technique. Six main domains provided by Beck’ Depression Scale were evaluated; borderline clinical depression, extreme depression, mild mood disturbances, moderate depression, severe depression, ups and downs are consider normal. Data was analyzed through SPSS 23 using non-parametric statistics. RESULTS: Among 456 students, 261 are from public sector and 195 from private sector universities. Magnitudes of six domains were 7.89% borderline clinical depression, 3.29% extreme depression, 21.05% mild mood disturbances, 21.27% moderate depression, 6.14% severe depression and 40.35% ups and downs are considered normal, all these domains are non- signiﬁcant among universities. CONCLUSION: Examination of the overall assessment of Beck’s Depression Inventory revealed that majority of Pharm.D students are suﬀering from some kind of depression.